2007
DOI: 10.1016/j.annepidem.2007.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and its Impact on a Provincial Health System in Canada

Abstract: Purpose:The main focus of this study is to explore the relationship between body mass index (BMI) as a reflection of obesity its association with chronic disease, health services utilization and its impact on direct co ts to the health system, in the province of Newfoundland and Labrador. Methods:In a secondary analysis of the provincial component ofthe Canadian Community Health Survey version 1.1 (2000/01 ), survey records for respondents aged 20-64 (n=2345) were linked to provincial physician and hospitaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In addition to providing detailed information allowing patient-specific costing of each encounter, inpatient databases record diagnostic and procedural information using the ICD-10-CA and CCI classification systems [62]. Using unique provincial health insurance numbers, the NLCHI will link the bariatric clinical/research data with administrative health services data and provide the research team with a de‐identified database of health services use and costs for data analysis purposes [63, 64]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition to providing detailed information allowing patient-specific costing of each encounter, inpatient databases record diagnostic and procedural information using the ICD-10-CA and CCI classification systems [62]. Using unique provincial health insurance numbers, the NLCHI will link the bariatric clinical/research data with administrative health services data and provide the research team with a de‐identified database of health services use and costs for data analysis purposes [63, 64]. …”
Section: Methodsmentioning
confidence: 99%